Depletion of the transcriptional coactivators megakaryoblastic leukaemia 1 and 2 abolishes hepatocellular carcinoma xenograft growth by inducing oncogene‐induced senescence. Issue 9 (29th July 2013) - Hampl, Veronika; Martin, Claudia; Aigner, Achim; Hoebel, Sabrina; Singer, Stephan; Frank, Natalie; Sarikas, Antonio; Ebert, Oliver; Prywes, Ron; Gudermann, Thomas; Muehlich, Susanne
<x xml:space="preserve">Abstract</x> Megakaryoblastic leukaemia 1 and 2 (MKL1/2) are coactivators of the transcription factor serum response factor (SRF). Here, we provide evidence that depletion of MKL1 and 2 abolishes hepatocellular carcinoma (HCC) xenograft growth. Loss of the tumour suppressor deleted in liver cancer 1 (DLC1) and the subsequent activation of RhoA were prerequisites for MKL1/2 knockdown‐mediated growth arrest. We identified oncogene‐induced senescence as the molecular mechanism underlying the anti‐proliferative effect of MKL1/2 knockdown. MKL1/2 depletion resulted in Ras activation, elevated p16 expression and hypophosphorylation of the retinoblastoma (Rb) protein in DLC1‐deficient HCC cells. Interestingly, reconstitution of HuH7 HCC cells with DLC1 also induced senescence. Evaluation of the therapeutic efficacy of MKL1/2 knockdown in vivo revealed that systemic treatment of nude mice bearing HuH7 tumour xenografts with MKL1/2 siRNAs complexed with polyethylenimine (PEI) completely abolished tumour growth. The regression of the xenografts was associated with senescence. Importantly, PEI‐complexed MKL1 siRNA alone was sufficient for complete abrogation of HCC xenograft growth. Thus, MKL1/2 represent promising novel therapeutic targets for the treatment of HCCs characterized by DLC1 loss.